A multifactorial approach to overuse running injuries: A 1-year prospective study - Winter, S. C.; Gordon, S.; Brice, S. M.; Lindsay, D.; Barrs, S. (Sports Health: A Multidisciplinary Approach, 2020)
Background: Because of the complex and multifaceted nature of running injuries, a multifactorial approach when investigating running injuries is required.